Studi Literatur Pemilihan Kosmetik Perawatan Kulit Kepala dan Rambut Berdasarkan Tingkat Kerusakannya Akibat Proses Styling - Eny Widhia Agustin; Ifa Nurhayati; Desia Nova Tiara; Intan Amalya Putri; Wanda Zefanya Maharani; Nadhiefa Dhiyaa Rizqy Zulfia; Dini Wulandari (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Stages in hair styling, such as hair coloring, straightening, the use of styling tools and chemicals in hair styling products often over time can cause damage to the scalp and hair. The level of this damage varies, ranging from dry hair to breakage, as well as irritation of the scalp. This study aims to review and determine the right scalp and hair care cosmetics with the level of damage caused to the styling process. The method used is a literature study by reviewing various scientific sources and recommendations for treatment products. The results of the study prove that treatments based on moisturizers, proteins, and natural ingredients are effective in tackling mild to severe hair damage. Meanwhile, for irritated scalps, products with anti-inflammatory and sulfate-free ingredients are recommended. In conclusion, the selection of cosmetics should be adjusted to the degree of hair damage and the condition of the scalp for optimal results.